2004
DOI: 10.1111/j.1740-0929.2004.00198.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of slaughter age on the levels of free amino acids and dipeptides in fattening cattle

Abstract: The effects of slaughter age, breed type and postmortem period were studied on the concentrations of free amino acids (FAA) and dipeptides (carnosine and anserine) in Longissimus dorsi muscle of beef. Slaughter age affected the levels of most FAA and dipeptides, and the concentrations of these compounds were significantly lower at 35 months of age than either 15 or 25 months of age. Slight increases were observed at 25 months compared with 15 months, but the differences were not significant except for a few FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 13 publications
3
28
0
Order By: Relevance
“…Wong et al (2008) reported that aspartic acid produced a fruity, pleasant, and sweet aroma by the Maillard reaction with glucose after heating, but that histidine did not produce any aroma. A previous study reported that an increase in the slaughter age of Wagyu cattle (15, 25, and 35 mo) led to accumulation of fat in the muscle and to low muscle growth, which resulted in decreased total amounts of free amino acids, and differences in some amino acid contents in the LD muscle (Watanabe et al, 2004). In that study, aspartic acid contents decreased with increasing slaughter age (Watanabe et al, 2004).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Wong et al (2008) reported that aspartic acid produced a fruity, pleasant, and sweet aroma by the Maillard reaction with glucose after heating, but that histidine did not produce any aroma. A previous study reported that an increase in the slaughter age of Wagyu cattle (15, 25, and 35 mo) led to accumulation of fat in the muscle and to low muscle growth, which resulted in decreased total amounts of free amino acids, and differences in some amino acid contents in the LD muscle (Watanabe et al, 2004). In that study, aspartic acid contents decreased with increasing slaughter age (Watanabe et al, 2004).…”
Section: Resultsmentioning
confidence: 66%
“…A previous study reported that an increase in the slaughter age of Wagyu cattle (15, 25, and 35 mo) led to accumulation of fat in the muscle and to low muscle growth, which resulted in decreased total amounts of free amino acids, and differences in some amino acid contents in the LD muscle (Watanabe et al, 2004). In that study, aspartic acid contents decreased with increasing slaughter age (Watanabe et al, 2004). When the carcass weights were considered, it can be expected that the slaughter age of Hanwoo steers of yield grade C may be older than that of yield grade A.…”
Section: Resultsmentioning
confidence: 99%
“…Watanabe et al (2004) observed that almost all FAA were lower in 35-monthold steers compared with younger steers, suggesting that well-fattened steers had lower FAA because of the lower muscle growth at the end of fattening. The increase in amino acids in beef during storage is lower than that of pork and chicken (Nishimura et al 1988b).…”
Section: Free Amino Acids Concentrationsmentioning
confidence: 90%
“…FAA concentrations are affected by meat aging, breed type, animal age (Watanabe et al 2004), pH, and the activity of proteases (Nishimura et al 1988a), and some of these FAA contribute to meat taste (Nishimura et al 1988b). There are, however, few reports about the relationship between FAA concentrations and intramuscular fat.…”
Section: Free Amino Acids Concentrationsmentioning
confidence: 99%
“…These amino acids increase with ageing (Watanabe, Ueda, & Higuchi, 2004) over 10 days. As there were no differences between treatments or operators in the concentration of these amino acids, this suggests that the tenderising effect seen with VFC2 tender was due to an influence of energy metabolism and not proteolysis during the first 24 h post mortem.…”
Section: Accepted Manuscriptmentioning
confidence: 97%